ニーオルスン デノ スカイラジオメータ カンソク ニ モトヅク 2006 ネン オヨビ 2007 ネン ノ シュンキ エアロゾル ノ コウガク トクセイ - 塩原, 匡貴; シオバラ, マサタカ; 矢吹, 正教; ヤブキ, マサノリ; 山野, 牧; ヤマノ, マキ; 青木, 一真; アオキ, カズマ; 小林, 拓; コバヤシ, ヒロシ; Shiobara, Masataka; Yabuki, Masanori; et al. (2010)
P(論文) 北極・ニーオルスンでは2000年3月よりPOM-01型,2004年5月よりPOM-02型のスカイラジオメータを用いた太陽放射の分光観測が行われている.スカイラジオメータによる波長400,500,675,870および1020 nmでの太陽直達光および天空光強度分布の測定データから,気柱エアロゾルの光学的厚さ,単散乱アルベド,複素屈折率等の光学特性を求めた.得られた結果から平常時とスモーク時との光学特性の違いを調べた.2006年春のスモーク到来時には極度に高い光学的厚さを示し,吸光性粒子の混入を示す結果となった.解析の結果得られたエアロゾルの複素屈折率と粒径分布により,スモーク時には平常時の硫酸性粒子や海塩粒子に加えて,煤や植物燃焼起源のエアロゾル粒子が存在することが示唆された. Sky-radiometer measurements have been performed in Ny-Alesund with Prede POM-01 since March 2000, and followed by POM-02 since May 2004. Aerosol optical properties, i.e., optical thickness, single scattering albedo and refractive index for selected wavelengths at 400, 500, 675, 870 and 1020 nm, and the volume size distribution, are retrieved from spectral measurements of the direct solar attenuation and the sky radiance distribution by sky-radiometer. These optical properties are compared for normal conditions and a smoke event in spring 2006. The result shows extremely high optical thickness and contamination of light absorbing particles for the smoke event. It is suggested from retrievals of the refractive index and size distribution that aerosol during the smoke event included soot and organics origin particles in addition to sulfate and sea-salt particles that are dominant for normal conditions. departmental bulletin paper